Hibiscus sabdariffa aqueous extracts pevents pogression of aute lver ijury iduced by aetaminophen - Ahmad Raus, Raha; Jamal, Parveen; Mohd-Isa, Emy Sazri (Universiti Putra Malaysia Press, 2012)
Hibiscus sabdariffa (local name Roselle) is usually used as a beverage in Southeast Asia. It has been shown that this plant has benefits to the health in term of improving diabetes and hiperlipidemia conditions. In this study, the effect of H. sabdariffa aqueous extracts in preventing acute liver injury progression in rats induced by acetaminophen (or paracetamol, PCM) was investigated. Results of the current study showed that intravenous injection of PCM at 1000 mg/kg induced lipid proxidation (malonaldehyde, MDA) and deteriorated liver marker enzymes (alanin transaminase, ALT and glutathione S-transferase, GST), as well as liver glutathione (GSH) and liver morphology. Feeding H. sabdariffa extract orally (500 or 1000 mg/kg) for three days after the PCM treatment was found to have significantly reduced lipid peroxidation. The depleted GSH observed in the affected liver returned to almost normal, while the liver marker enzyme, ALT and GST levels were improved by giving the extract. In histological examination, the H. sabdariffa extract was shown to have reduced the incidence of liver damage. However, a high dose of H. sabdariffa treatment to the untreated rats increased liver MDA and GST and serum ALT levels, although at a much lower level than the PCM-treated rats. Hence, the liver histology of these rats remains normal. In conclusion, the current study has shown that the post-treatment of H. sabdariffa prevents the progression of acute liver damage induced by PCM. However, the consumption of the plant at high dosage should be taken with caution.